2012
DOI: 10.1371/journal.pcbi.1002382
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Evidence Integration in Rapid Decision Processes

Abstract: Decisions about noisy stimuli require evidence integration over time. Traditionally, evidence integration and decision making are described as a one-stage process: a decision is made when evidence for the presence of a stimulus crosses a threshold. Here, we show that one-stage models cannot explain psychophysical experiments on feature fusion, where two visual stimuli are presented in rapid succession. Paradoxically, the second stimulus biases decisions more strongly than the first one, contrary to predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…In a recent study, we investigated decision making with the one vernier fusion paradigm, i.e., a no compelled response paradigm. We found that accuracy and reactions times were not easily be explained with classical one-stage models [24]. For this reason, we proposed a two-stage model in which evidence integration and the race-to-threshold are not one and the same process in accordance with previous findings [25][27].…”
Section: Discussionsupporting
confidence: 53%
“…In a recent study, we investigated decision making with the one vernier fusion paradigm, i.e., a no compelled response paradigm. We found that accuracy and reactions times were not easily be explained with classical one-stage models [24]. For this reason, we proposed a two-stage model in which evidence integration and the race-to-threshold are not one and the same process in accordance with previous findings [25][27].…”
Section: Discussionsupporting
confidence: 53%
“…Hence, information persistence in a buffer stage might explain why Prime 2 remains dominant even when Prime 1 has a head start long enough to provoke a high rate of response errors under conditions of speeded instead of delayed responding. Such a twostage model was recently proposed for decision making (Rüter, Marcille, Sprekeler, Gerstner, & Herzog, 2012;Rüter, Sprekeler, Gerstner, & Herzog, 2013;Scharnowski, Hermens, Kammer, Ogmen, & Herzog, 2007) and is supported by transcranial magnetic stimulation experiments, which show that vernier fusion takes up to 400 ms (Rüter, Kammer, & Herzog, 2010;Scharnowski et al, 2009).…”
Section: Discussionmentioning
confidence: 83%
“…() and Rüter et al. () compared one‐stage and two‐stage models of conflict and selection. In one‐stage models the perceptual evidence feeds directly into those units that compete for selection, whereas in two‐stage models competing units receive perceptual evidence only after pre‐processing (e.g., after evidence accumulation has terminated).…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Rüter et al. () and Purcell et al. () both indicate that two‐stage models are more appropriate than one‐stage models.…”
Section: Discussionmentioning
confidence: 99%